EKSPLORASI ETNOMATEMATIKA PADA CANDI JABUNG DI KABUPATEN PROBOLINGGO - Husnul Hotimah; Nur Wiji Sholikin (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This research aims to identify and analyze the mathematical elements applied in the architecture of Jabung Temple, Probolinggo Regency. This research uses qualitative research methods with an ethnographic approach. The results of the research show that there are several ethnomathematics at Jabung Temple, including the concepts of flat shapes, spatial shapes, geometric transformations, similarity and congruence. This research can be used as material for preparing student test packages in the form of questions related to geometric transformations. This research can also help improve students' ability to understand mathematical concepts and develop critical and logical thinking skills. Apart from that, this research can also be a reference for teachers in developing curriculum and mathematics learning methods that are more effective and enjoyable for students.